Paleo Isobaths in 3D Seismic Exploration Data Uncover Submerged Shorelines From Glacial Lowstands: A Case Study From the Levant Basin - Algon, R.; Medvedev, B.; Agnon, A. (Frontiers in Earth Science, 2022)
Modern petroleum exploration extracts 3D volumes of seismic data where certain curves can be drawn delimiting stratigraphic horizons. Such curves hold a promise as piercings for identifying tectonic offsets in 3D. Pinchout points on vertical sections connect with adjacent sections to form contours in 3D. Such a contour, showing quasi-uniform depth, may be considered a paleo-isobath. Here we focus on pinchout paleo-isobaths in the western shores of the Levant that might record ∼120 m drop in sea level at the peak of late Quaternary glacials. We identified a pinchout isobath, ∼15 km offshore, ∼140 m below sea level. Water depth averages ∼90 m, and sediment cover averages ∼45 m. Allowing for isostatic adjustment, this is compatible with eustatic levels of the last two glacial maxima. We hypothesize that the contour mapped is closely related to the shoreline of one of the last glacial maxima. The pinchout pattern is continuous for ∼25 km in the southern reaches of the survey area, at depths of 137 ± 2.5 m, an isobath within the observational uncertainty. The isobath is lost for ∼10 km in the central portion of the survey, north of which a slightly deeper isobath reappears for 7 km, until it disappears approaching a bathymetric trough. The deeper pinchout isobath reappears in the northernmost section of the survey, where it deepens by an average of 5–6 m relative to the southern part (from 137 m to 142 m). The deepening of the pinchout contour is consistent with massive sliding underlying the trough. Sliding here has been attributed to sediment load or salt tectonics, and has been recently associated with a local tsunami dating 9.6 ± 0.3 ka. Recent work relocated the deepest earthquakes on the Levant southern shelf (depths circa 30 km) to the trough, with epicenters coinciding with the boundary faults. This may indicate an active deep-seated tectonic feature. Expressions of the contour outside the survey area will offer tests to our paleo-shoreline hypothesis. Additional pinchout isobaths and pinchout contours associated with earlier lowstands will help constrain tectonic rates as well as glacial eustatic levels and hydro-isostatic effects, with potential regional and global applications.